Description of a Neotropical gall inducer on Araceae: Arastichus, gen. nov. (Hymenoptera, Eulophidae) and two new species - Zhang, Miles (2022)
A new genus of a Neotropical gall inducing tetrastichine eulophid on Araceae is described and confirmed using Ultraconserved Elements (UCE) phylogenomic data. Arastichus Gates, Hanson, Jansen-González & Zhang, gen. nov., includes two new species and one species transferred from Aprostocetus Westwood: A. capipunctata Gates, Hanson, Jansen-González & Zhang, sp. nov., A. gallicola (Ferrière), comb. nov., and A. gibernau, Gates, Hanson, Jansen-González & Zhang, sp. nov.